2020
DOI: 10.23865/noros.v34.2396
|View full text |Cite
|
Sign up to set email alerts
|

Russia’s Crony Capitalism. The Path from Market Economy to Kleptocracy

Abstract: Russia’s Crony Capitalism. The Path from Market Economy to KleptocracyAnders Åslund provides a systematic and thought-provoking account of how Russia under Putin has gone from a liberally oriented market economy to kleptocratic state capitalism. Much of the focus is on deinstitutionalization, which has undermined property rights and led to limitations of Russia’s growth potential. The narrative draws on a vast array of sources and Åslund’s unique personal experiences to provide a comprehensive picture of how R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Empirical studies found little support for either proposition in Russia during the 1990s (Gerber, 2000, 2002; Gerber & Hout, 1998). In fact, Russia diverged from a textbook market economy, instead developing “crony capitalism” (Aslund, 2019), where a handful of elites used political connections to amass fortunes by acquiring the lion's share of formerly state‐owned productive assets while most of the population's living standards were eroded by falling earnings, surging inflation, shrinking employment in heavy industries (favored by Soviet‐era planners but undermined by foreign competition), and eroding social welfare payments.…”
Section: The Labor Marketmentioning
confidence: 99%
“…Empirical studies found little support for either proposition in Russia during the 1990s (Gerber, 2000, 2002; Gerber & Hout, 1998). In fact, Russia diverged from a textbook market economy, instead developing “crony capitalism” (Aslund, 2019), where a handful of elites used political connections to amass fortunes by acquiring the lion's share of formerly state‐owned productive assets while most of the population's living standards were eroded by falling earnings, surging inflation, shrinking employment in heavy industries (favored by Soviet‐era planners but undermined by foreign competition), and eroding social welfare payments.…”
Section: The Labor Marketmentioning
confidence: 99%
“…Putin was able to build and maintain a strong regime in Russia through a combination of strategic economic policies and control over political institutions (Åslund, 2015;Jennings 2021). His government placed key sectors of the economy, such as energy and defence, under his direct control.…”
Section: Public Choice and The Context Of Russia Foreign Policy Forma...mentioning
confidence: 99%
“…In 2019, Anders Aslund examined the performance of key state corporations, such as Gazprom, Vneshekonombank, and Rostec, and concluded that Russia's brand of state capitalism is not associated with "long-term state plans for investment and technological development," and that Rostec's development appears to be a reflection of its CEO empire-building ambitions rather than economic efficiency or innovation considerations. 322 In the same vein, another set of authors analyzed Russian anti-access/area denial measures and concluded that Russia's ability to produce "technical miracles" will be limited by endemic cronyism and corruption. 323 Polina Beliakova and Sam Perlo-Freeman reviewed key cases of corruption in the Russian defense sector and noted that corruption remains a "significant problem facing the Russian arms industry," citing reports that MoD's secretive procurement was contributing to corruption.…”
Section: Institutions and The Innovation Environmentmentioning
confidence: 99%